Operations Research, Mathematics, Computer Science and Statistics: The Relationships - Adewoye S Olabode (Data Science: Journal of Computing and Applied Informatics, 2020)
Many people have difficulty in seeing any difference between Mathematics, Operations Research, Statistics, Computer Science and other disciplines while others are just plain confused. In this work, OR and its applications are being exposed and then compared in order to look into the relationships between OR, Mathematics, Computer Science, Statistics and other fields. It has been realized that all these areas of knowledge are also interrelated with other areas such as Engineering, Physics, Microbiology, Economics etc.